Persian Gulf 2019 - Kumaraswamy, P. R. author. aut Link
XVI, 283 p. 36 illus.
Keywords: The book is seventh in the annual Persian Gulf series published by MEI@ND. It is a comprehensive analysis of India’s bilateral relations with the nine countries in the Persian Gulf and the GCC and focusses on developments during 2018. It gives a comprehensive account of the strategic, political, economic and cultural aspects of bilateral developments and also provides in-depth analysis of internal dynamics of the Persian Gulf countries. The final chapter offers policy recommendations based on the current state of affairs. P. R. Kumaraswamy teaches contemporary Middle East in Jawaharlal Nehru University, New Delhi and is Honorary Director, Middle East Institute, New Delhi, India. In February 2010, he set up the virtual Middle East Institute, New Delhi and serves as its honorary director. He is the editor of Contemporary Review of the Middle East and the series editor of Persian Gulf: India’s Relations with the Region. Md. Muddassir Quamar is Associate Fellow, Institute for Defense Studies & Analyses, New Delhi, India. Dr. Quamar was a visiting fellow in King Faisal Center for Research and Islamic Studies, Riyadh and serves as Associate Editor of Contemporary Review of the Middle East.